Social Panorama of Latin America 2019 - United Nations (United Nations, 2020)
The Social Panorama of Latin America 2019 analyzes issues crucial to understanding and action given the structural challenges facing the countries of Latin America and the Caribbean in the current economic and social situation, especially in the context of the transformations underway in labour markets. Throughout the report, which has been published since 1991, strategies and policies are suggested for advancing toward inclusive development in accordance with the 2030 Agenda for Sustainable Development.